PEMBERIAN BERBAGAI KONSENTRASI AIR KELAPA PADA BIBIT KOPI ROBUSTA (Coffea canephora Pierre) - Adlan ' Amsyahputra; Adiwirman ' '; Nurbaiti ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims to determine the influence of the concentration of coconut water, to find out the best concentration for the growth of seedlings of robusta coffee plant and look for correlation of all parameters on the treatment that gives the highest growth. This research has been carried out in the UPT area of research farm in the faculty of agriculture, University of Riau. This research was conducted in June to September. This design of this research was completely random design, 5 treatments and 4 replications. Each research unit consists of 3 plants, thus the number of sources used as many as 60 robusta coffee seeds. The results showed that an increase in the concentration of coconut water also improves the increment of plant height, the increase in the circumference of the trunk, broad leaves, root header ratio and dry weight of the plant. The results showed that an increase in the concentration of coconut water doesn't improve the increment of the number of leaves. Treatment of the application of the coconut water with a concentration of 50% gives the highest influence for the increment of plant height, the increase in the circumference of the trunk, broad leaves, root header ratio and dry weight of the robust coffee plant. The plant's dry weight is correlated very strongly with the increment of the number of leaves, broad leaves and root shoot ratio. Plant dry weight correlated strongly with the increase in the circumference of the trunk and the increment of plant height. Keywords: coconut water, seeds, robusta coffee